2007
DOI: 10.1562/0031-8655(2003)0770265ureoca2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation Exposure of Children and Adolescents in Durban, South Africa¶

Abstract: The solar ultraviolet radiation (UVR) exposure of 30 children and adolescents in three age groups (4–6 years, 7–9 years and 13–14 years) was measured for 1 week in late summer (February–March) in Durban, South Africa, using UVR‐sensitive polysulfone film badges (PSFB) attached to the lapel region of the body. The mean and median values for all ages over the study period were 2.0 and 1.2 standard erythemal dose (SED) units, respectively, where 1 SED = 100 J·m−2. Individual PSFB doses were analyzed as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Studies have found that schoolchildren and outdoor workers may receive about 5% and 20% of the total daily ambient solar UVR received on a horizontal surface respectively. Indeed, in a rudimentary South African study, children received ca 5% of the total daily ambient solar UVR , a finding consistent with similar studies among schoolchildren in New Zealand , Denmark and England .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies have found that schoolchildren and outdoor workers may receive about 5% and 20% of the total daily ambient solar UVR received on a horizontal surface respectively. Indeed, in a rudimentary South African study, children received ca 5% of the total daily ambient solar UVR , a finding consistent with similar studies among schoolchildren in New Zealand , Denmark and England .…”
Section: Introductionsupporting
confidence: 80%
“…To date, no attempts have been made to empirically determine (or estimate) the nonintegrated, personal solar UVR exposure of children and outdoor workers in South Africa and Reunion Island to assess sunburn risk. In South Africa, a desktop study characterized nonmelanoma skin cancer risk for outdoor workers as being high and schoolchildren's cumulative sun exposure was found to be relatively high using polysulfone film . Two studies have estimated sunburn risk among susceptible groups at several sites in South Africa , but no evidence of similar studies was found for Reunion Island.…”
Section: Introductionmentioning
confidence: 99%
“…This gave an equivalent incremental standard erythemal dose (SED) (1 SED = 100 J cm −2 ) of 2.16 to 17.3 SED. This work was carried out in Durban, South Africa, a region that receives daily total ambient erythemal ultraviolet radiation of about 60 SEDs during summer . Each exposed sample was contained in a stoppered 1.00 mm pathlength quartz cuvette.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we collected UV exposure data from 28 Danish volunteers (13 males and 15 females), median age 39 years (range 4-70) visiting popular sunny holiday resorts in the winter half-year for a median of 7 days (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These subjects were indoor workers from the staff of the department or family or friends of the staff.…”
Section: Study Populationmentioning
confidence: 99%
“…4 In Australia (19°S) and South Africa (30°S) other groups performed just short-term dosimeter studies during the summer season. [5][6][7] In the Netherlands (52°N) estimates of annual UV radiation exposure are mainly derived from ambient measurements, 8 while in the U.K. (50-55°N) estimates of annual UV doses are primarily based on mannequin studies and personal dosimetry of children during a spring season. 9 We previously described the Danes' UV exposure pattern in the summer half-year using time-stamped personal UV dosimetry, sun behaviour diaries and questionnaires.…”
mentioning
confidence: 99%